FAKTOR – FAKTOR YANG MEMPENGARUHI PURCHASE INTENTION PRODUK BERAS PORANG DI KOTA TANGERANG SELATAN - Arsyi, Baginda; Agustina Shinta Hartati Wahyuningtyas; Suhartini (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
Changes in the consumption patterns of modern society show an increasing interest in healthier foods. Consumers are becoming increasingly selective in determining the foods they will consume. One product that is being widely discussed is porang rice. Porang rice is believed to have lower calorie and glucose content with higher fiber content compared to rice, making it good for diabetics or those on a diet program.  This study aims to determine the determinants that influence the intention to buy porang rice products in South Tangerang City using a theoretical framework based on the extended theory of planned behavior (TPB) model. This research uses a quantitative approach with the structural equation model-partial least square (SEM-PLS) analysis method with SmartPLS 4.0 software. The method of determining the sample in this study using non-probability sampling techniques with purposive sampling method with a total research sample of 100 respondents. The results showed that the variables of product knowledge and awareness of health had a positive and significant effect on attitudes towards porang rice, but product knowledge had a positive but insignificant effect on purchase intention. variables of awareness of health, subjective norms, perceived behavioral control and attitudes towards porang rice had a positive and significant effect.